GREEN TECHNOLOGY ADOPTION IN INDONESIAN INDUSTRIES: DRIVERS, CHALLENGES, AND PERFORMANCE IMPLICATIONS - Herry Achmad Buchory; Uce Karna Suganda; Ijang Faisal (PT. Kreatif Indonesia Satu, 2024)
Background: Indonesia faces environmental pressures from rapid industrialization. Green technology adoption offers solutions for reducing emissions and improving resource efficiency, yet adoption remains uneven across sectors. Aims: This study investigates drivers, barriers, and performance implications of green technology adoption in Indonesian industries. Research Method: A mixed-methods approach combined surveys of 198 firms across five sectors with 25 in-depth interviews. Data were analyzed using PLS-SEM and thematic analysis. Results and Conclusion: Regulatory pressure (β=0.38), customer demand (β=0.41), and cost benefits (β=0.35) drive adoption. Major barriers include high costs (71%), lack of expertise (64%), and insufficient support (59%). Adopters reported 26% emissions reduction, 32% energy efficiency gains, 23% water conservation, and 29% waste reduction. Comprehensive policies, incentives, and capacity building are needed to accelerate adoption. Contribution: This research provides empirical evidence on green technology adoption in developing economies, offering insights for policymakers and industry practitioners.